Strategies to Encourage Adoption of Stormwater Pond Best Management Practices (BMPs) by Homeowners - Emily Ott; Paul Monaghan; Ondine Wells; Gail Hansen; Laura Warner; Michelle Atkinson (EDIS)
Man-made ponds can be a useful way to collect, store, and treat stormwater runoff in residential areas. However, these ponds can become polluted when runoff contains fertilizers, pesticides, and pet waste from the neighborhood. This 9-page fact sheet outlines several best management practices (BMPs) for reducing stormwater pond pollution. Based on a survey of residents who live near stormwater ponds, the authors recommend strategies Extension educators can use to encourage residents to adopt these BMPs. Written by Emily Ott, Paul Monaghan, Ondine Wells, Gail Hansen, Laura Warner, and Michelle Atkinson, and published by the UF Department of Agricultural Education and Communication, July 2015.